Russia’s invasion of Ukraine threatens food security in Malawi: How can the country respond? - De Weerdt, Joachim; Duchoslav, Jan (International Food Policy Research Institute, 2023)
Food insecurity is endemic in Malawi, affecting up to 38% of the population every year in the run-up to the harvest in April. Although geographically distant, there are multiple channels through which Russia’s invasion of Ukraine can make matters worse this year. The conflict has disrupted global supplies of key cereals, vegetable oils, and fertilizers, pushing already-high prices higher, and putting particular pressure on low-income countries with vulnerable poor populations. In this post we discuss how rising wheat, maize, cooking oil, and fertilizer prices are likely to impact Malawi and how the government can respond.